Prediction of High-Grade Vesico-Ureteral Reflux after a First Urinary Tract Infection in Children: External Validation of a Clinical Decision Rule - Leroy, S.; Bouissou, F.; Fernandez, A.; Gurgoze, M.; Karavanaki, K.; Ulinski, T.; Chalumeau, M. (Springer, 2010)
[Abstract Not Available]